The Role of Product Diversity, Product Quality, Price and Service Quality on Swallow's Nest Purchasing Decisions: A Study of Swallow Companies in West Sulawesi - Wijaya, Patrick Natalion; Harianto, Eric; Judi, Tjatur Ermitajani; Aisah, Nurul (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study discusses the effect of product diversity, product quality, price and service quality on swallow's nest purchasing decisions at the WWALET company study in West Sulawesi, this research uses quantitative methods with multiple regression designs. The population used in this study were consumers of WWALET companies with purposive sampling technique. The participants who participated in this study were 61 participants with the characteristics of consumers who had or knew swallow nest products in Surabaya. The research was conducted by distributing questionnaires in the form of Google Forms online in communities that know swallow nest products. In this study, hypothesis testing used multiple regression analysis with the help of SPSS. The results found that price is a variable that has a significant effect on purchasing decisions. Where the price affordability factor that is in line with the quality and usefulness of the product is an attraction for consumers to buy swallow's nest products. The implications of the results of this study can be useful in determining prices by WWALET, such as paying attention to the factors of affordability, price suitability, usability, competitiveness in the swallow nest market in the Surabaya area.